Development of a quantitative thyroid-stimulating hormone assay system for a benchtop digital ELISA desktop analyzer - Arai, Yoshiyuki; Wang, Dong; Takeuchi, Miki; Utsunomiya, Sosuke; Degawa, Takuma; Kai, Atsushi; Ichikawa, Hisashi; Chiba, Ryotaro; Yoshimura, Toru (Frontiers in Bioengineering and Biotechnology, 2023)
Regular checkups for thyroid-stimulating hormone (TSH) levels are essential for the diagnosis of thyroid disease. The enzyme-linked immunosorbent assay (ELISA) technique is a standard method for detecting TSH in the serum or plasma of hospitalized patients. A recently developed next-generation ELISA, the digital immunoassay (d-IA), has facilitated detection of molecules with ultra-high-sensitivity. In this study, we developed a TSH assay system using the d-IA platform. By utilizing the ultrasensitivity of d-IA, we were able to use a sample volume of as little as 5 µL for each assay (the dead volume was 5 µL). The limits of blank, detection, and quantification (i.e., functional sensitivity), were 0.000346, 0.001953, and 0.002280 IU/mL, respectively, and the precision of the total coefficient of variation did not exceed 10%. The correlation between serum and plasma levels indicated good agreement. Thus, our system successfully measured TSH using d-IA with a small sample volume and equal functional sensitivity to the current third generation like ARCHITECT TSH assay, which has a functional sensitivity of 0.0038 IU/mL.